2023
DOI: 10.1111/inm.13136
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of grief symptoms and disorders in the time of COVID‐19 pandemic: A meta‐analysis

Abstract: Millions of people worldwide are mourning the loss of loved ones due to the COVID-19 epidemic, which may adversely impact their mental health. This metaanalysis aimed to investigate pandemic grief symptoms and disorders for developing policy, practice, and research priorities. The databases of Cochrane, Embase, Ovid-MEDLINE, WHO COVID-19, NCBI SARS-CoV-2, Scopus, Web of Science, CINAHL, and Science Direct were comprehensively searched until July 31, 2022. The Joanna Briggs Institute's and Hoy's criteria were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The pooled prevalence rate of grief symptoms and disorder was determined to be 45.1% (95% confidence interval: 32.6% to 57.5%) and 46.4% (95% confidence interval: 37.4% to 55.5%), respectively. However, a significantly higher prevalence of grief symptoms and disorder was observed among healthcare workers, amounting to 56.6% and 57.0%, respectively, 12 13 14 and 57.6% of the study’s subjects were identified as experiencing complicated grief during the pandemic. 15 …”
Section: Introductionmentioning
confidence: 77%
“…The pooled prevalence rate of grief symptoms and disorder was determined to be 45.1% (95% confidence interval: 32.6% to 57.5%) and 46.4% (95% confidence interval: 37.4% to 55.5%), respectively. However, a significantly higher prevalence of grief symptoms and disorder was observed among healthcare workers, amounting to 56.6% and 57.0%, respectively, 12 13 14 and 57.6% of the study’s subjects were identified as experiencing complicated grief during the pandemic. 15 …”
Section: Introductionmentioning
confidence: 77%
“…It is reported by a meta-analysis that the prevalence of grief symptoms and disorders during the COVID-19 pandemic is as high as 45.8% ( 47 ). Providing support and effective interventions to help those grieving develop coping mechanisms is crucial for their recovery ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 The grief responses of firefighters are an issue that requires attention but has not yet been addressed in this pandemic. Healthcare workers reported that their grief response was higher 15 and associated with their mental health. 16 Like healthcare workers, 17 firefighters were witnesses and victims.…”
Section: Pandemic Grief Reaction and Intolerance Of Uncertainty On Th...mentioning
confidence: 99%